Monitoring bovine fertility through qualitative assessment of milk progesterone - Pandit, R K; Chauhan, R A S (The Indian Journal of Animal Sciences, 2012)
Confirmation of oestrus, early pregnancy and differentiation of ovarian cysts was done using enzyme-linked immunosorbant assay (ELISA). Milk samples (119) from 69 animals were tested with the accuracy of detecting oestrus as 96.66% in cows and 100% in buffaloes. Detection of pregnancy, 19 day-post-service was 94.11% accurate in cows and 86.66% in buffaloes. Diagnosis of non-pregnancy was 100% accurate in cows and 80.00% in buffaloes. Differentiation of ovarian cysts by ELISA and gynaecoclinical palpations revealed better confirmation by the former, as the error was more by the latter in diagnosing luteal (44.44%) and follicular (10.00%) cysts.